Education and writing: In evidence the characteristics and examples of linguistic-discursive operations - Balieiro , Luan Tarlau (Seven Editora, 2023)
The main purpose of this text is to characterize the linguistic-discursive operations by means of examples elaborated by the author himself. Based on the theoretical assumptions of Applied Linguistics and studies on text rewriting, it aims to exemplify each linguistic-discursive operation and analyze how it is systematized in the rewriting process. In order to do so, it is problematized the fact of the student attend or not the reformulations suggested by the teacher in the revision and rewriting practices. The conclusion is that writing is a continuous action, in which the first version of a text cannot be defined as a finished product with the sole purpose of being evaluated by the teacher. It becomes important to conceive the text as a space for reflections, revisions, rereading, and rewriting, in an interlocutory process between teacher and student. DOI:https://doi.org/10.56238/ptoketheeducati-039